The role of boron in prevention of osteoarticular diseases and its distribution in the Republic of Moldova (One Health & Risk Management, 2021)
Introduction. Boron is a trace mineral that is supposed to be essential for human health. Organic plant based boron compounds are highly bioavailable for humans and can positively influence minerals such as calcium, phosphorus, magnesium and act in synergy with vitamin D, which are beneficial for osteoarticular health. Material and methods. We made an analysis of 126 bibliographic sources and mapped the Republic of Moldova to the content of boron in deep water and to the adults’ prevalence of rheumatoid arthritis and inflammatory polyarthropathy. Results. Boron is important for osteogenesis and its deficiency can lead to impaired growth and abnormal bones development. It supports bone health in postmenopausal women by reducing urinary loss of the minerals such as calcium, magnesium and phosphorus, which are essential for bone building. In countries where soil was depleted of boron and daily intake of this mineral was 1 mg or lower, the incidence of arthritis was between 20 and 70%. In Moldova, in the regions where boron concentration in deep drinking water were low (0.28 mg/L in well water and 0.51 mg/L in artesian well water) in Soroca in 2019, the prevalence with the rheumatoid arthritis and inflammatory polyarthropathy were high (51.6 per 10000 inhabitants) with one exception, UTA Gagauzia (35.1 per 10000 inhabitants), where we found a high boron concentration in deep drinking water (2.05 mg/L in well water and 2.2 mg/L in artesian well water) in 2015. Conclusions. Boron can affect bone metabolism. In regions where boron concentration in deep drinking water is low, the osteoarticular morbidity can be higher with the exception of UTA Gagauzia, where we suppose that dietary pattern can be a cause of these results. In the future we will study eating habits in this region and a clearer conclusion will be made.
Keywords: osteoarticular diseases; boron; boron compounds.